Integration Of Smart Infrastructure Systems And Innovative Materials To Enhance Sustainability, Performance, And Resilience In Modern Civil Engineering - Zebua, Dermawan; Giawa, Jun Fajar Krisman; Waruwu, Julfan Putra (Innovative Research in Civil and Environmental Engineering, 2025)
The rapid development of digital technologies and advanced material innovations has transformed the field of modern civil engineering. This study examines the integration of smart infrastructure systems with innovative construction materials to enhance structural performance, sustainability, and resilience. Using a mixed-methods approach, the research combines expert interviews, case studies, and quantitative data from 30 infrastructure projects implemented between 2018 and 2024. The results indicate that smart infrastructure equipped with real-time monitoring, IoT sensors, and AI-based predictive analytics significantly reduces maintenance frequency by up to 40% and improves reliability through early detection of structural anomalies. Meanwhile, innovative materials such as self-healing concrete, fiber-reinforced polymers (FRP), and geopolymer composites demonstrate substantial improvements in durability, mechanical strength, and carbon footprint reduction—achieving up to 70% lower CO₂ emissions compared to traditional materials. Life cycle assessments further confirm the long-term economic benefits of implementing smart and sustainable systems, despite higher initial investment costs. The study concludes that the integration of intelligent technologies and next-generation materials constitutes a paradigm shift that supports global sustainability goals, enhances infrastructure resilience, and drives the transition toward smarter, greener urban environments.